Legal Aspects of Economic Integration in Africa / Richard Frimpong Oppong. - Oppong, Richard Frimpong, 1978- (Cambridge University Press, 2011)
Richard Frimpong Oppong challenges the view that effective economic integration in Africa is hindered by purely socio-economic, political and infrastructural problems. Inspired by the comparative experiences of other regional economic communities and imbued with insights from constitutional, public and private international law, he argues that even if the socio-economic, political and infrastructural challenges were to disappear, the state of existing laws would hinder any progress. Using a relational framework as the fulcrum of analyses, he demonstrates that in Africa's economic integration processes, community-state, inter-state and inter-community legal relations have neither been carefully thought through nor situated on a solid legal framework, and that attempts made to provide legal framework have been incomplete and, sometimes, grounded on questionable assumptions. To overcome these problems and aid the economic integration agenda that is essential for Africa's long-term economic growth and development, the author proposes radical reforms to community and national laws.